La conceptualisation et la place des concepts pragmatiques dans l’activité professionnelle et le développement des compétences - Christine Vidal-Gomel; Janine Rogalski (Activités)
The aim of the paper is to analyse the place of conceptualisation in professional activities, and to specify the notion of « pragmatical concept » (Samurçay, & Pastré, 1995), which plays a key role in professional didactics, as a component of professional competence and as an organiser of the activity at work. The history of the notion is briefly presented, and the various approaches – directly or indirectly – dealing with the issue of conceptualisation for action are discussed. Then, the paper develops the relationships and differences between – on the one hand – pragmatical concepts and the concepts of science and technics, and – on the other hand – everyday or « spontaneous » concepts. We discuss then the theoretical place respectively played by pragmatical concepts in professional didactics and « concepts-in-action » in disciplinary didactics (mathematics: Vergnaud, 1990). Finally, we propose some examples of how the issue of conceptualisation for action may be used in the design of operative cognitive tools, which are specific type of tools for supporting professional work.